THE EFFECT OF LANGUAGE LEARNING STRATEGIES TRAINING TOWARD STUDENTS’ READING ACHIEVEMENT OF SMA NEGERI 8 BULUKUMBA - Marzuki, Mutmainnah (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
The objectives of the research were to find out (1) the language learning strategies are dominantly used by the students, (2) the significant difference of the students’ reading improvement between the students who were given language learning strategies training and who were not given language learning strategies training, and (3) whether or not there is any effect of dominant language learning strategies used by the students toward their reading achievement. The results of this research showed that (1) the social strategies were marked as the highest usage or the dominant strategies used by the students and followed by metacognitive strategies, (2) there was significant difference of the students’ reading improvement between the students who were given the language learning strategies training and who were not given the language learning strategies training, and (3) there was not an effect of dominant of language learning strategies training (metacognitive and social strategies) simultaneously toward the students’ reading achievement. Meanwhile, in detail analysis or partial analysis showed that only social strategies had an effect toward the students’ reading achievement, but for metacognitive strategies had not an effect toward the students’ reading achievement.